Serum creatine kinase and creatinine in adult spinal muscular atrophy under nusinersen treatment. Issue 5 (31st March 2021) - Freigang, Maren; Wurster, Claudia D.; Hagenacker, Tim; Stolte, Benjamin; Weiler, Markus; Kamm, Christoph; Schreiber‐Katz, Olivia; Osmanovic, Alma; Petri, Susanne; Kowski, Alexander; Meyer, Thomas; Koch, Jan C.; et al.
Abstract: Objective: To determine whether serum creatine kinase activity (CK) and serum creatinine concentration (Crn) are prognostic and predictive biomarkers for disease severity, disease progression, and nusinersen treatment effects in adult patients with 5q‐associated spinal muscular atrophy (SMA). Methods: Within this retrospective, multicenter observational study in 206 adult patients with SMA, we determined clinical subtypes (SMA types, ambulatory ability) and repeatedly measured CK and Crn and examined disease severity scores (Hammersmith Functional Motor Scale Expanded, Revised Upper Limb Module, and revised Amyotrophic Lateral Sclerosis Functional Rating Scale). Patients were followed under nusinersen treatment for 18 months. Results: CK and Crn differed between clinical subtypes and correlated strongly with disease severity scores (e.g., for Hammersmith Functional Motor Scale Expanded: (CK) ρ  = 0.786/ (Crn) ρ  = 0.558). During the 18 months of nusinersen treatment, CK decreased (∆CK = −17.56%, p  < 0.0001), whereas Crn slightly increased (∆Crn = +4.75%, p  < 0.05). Interpretation: Serum creatine kinase activity and serum creatinine concentration reflect disease severity of spinal muscular atrophy and are promising biomarkers to assess patients with spinal muscular atrophy during disease course and to predict treatment response. The decrease of creatine kinase activity, combined with the tendency of creatinine concentration to increase during nusinersen treatment, suggests reduced muscle mass wasting with improved muscle energy metabolism.